New insights into immunomodulatory properties of lactic acid bacteria fermented herbal medicines - Zhu, Hongru; Guo, Lidong; Yu, Dan; Du, Xiaowei (Frontiers in Microbiology, 2022)
With the emerging of COVID-19, more attention has been focused on the immune system, which is essential to maintain human health. The immunomodulatory ability of traditional herbal medicine has been confirmed by a large number of clinical trials, and displays an obvious advantage, such as multiple targets and fewer side effects. The immunomodulatory active compounds of herbal medicines mainly included polysaccharides, saponins, flavonoids, and phenolics, which could be increased and may be modified to produce a new active compound after the fermentation of lactic acid bacteria (LAB). Meanwhile, as the main source of probiotics, LAB could produce some immunomodulatory active metabolites, such as exopolysaccharides, short chain fatty acids, and bacteriocins during the process of fermentation. Moreover, several compounds from herbal medicines could also promote the growth and production of immune active metabolites of LAB. Therefore, LAB-mediated fermentation of herbal medicines has become a new strategy to promote the regulation of the immune system in human. In this review, we discussed the immunomodulatory properties and active compounds of LAB fermented herbal drugs, the interaction between LAB and herbal medicines and changes in immunoregulatory active components during the fermentation, as well as the mechanisms of herbal medicines fermented by LAB on the regulating the immune system, including activation of innate or adaptive immune system and maintenance of intestinal immune homeostasis.